Treatment evaluation of odontogenic keratocyst by using CBCT and fractal dimension analysis on panoramic radiograph - Eha Renwi Astuti; Ni Putu Mira Sumarta; Ramadhan Hardani Putra; Berty Pramatika (Wolters Kluwer Medknow Publications, 2019)
The odontogenic keratocyst (OKC) is a benign intraosseous lesion that derives from remnants of the dental lamina. General practitioners usually use panoramic radiograph and cone-beam computed tomography (CBCT) as radiography examination of a suspected OKC lesion in the mandible or maxilla. Evaluation of post marsupialization could be assessed by using fractal dimension (FD) analysis of trabecular bone in panoramic radiograph and CBCT. In the present case, we use panoramic radiograph and CBCT for the treatment evaluation of OKC. The aim of this case report is to describe a case of OKC and evaluation of treatment progress by using FD analysis on panoramic radiograph and CBCT. A 40-year-old female patient came with a complaint of slowly enlarged swelling on the left mandible for 10 years. Low-grade pain occasionally happened to that women. Panoramic radiographs revealed multi-locular radiolucency extending from anterior of the mandible body to ascending ramus. Coronoid and condyloid process, and inferior border of the mandible were intact. OKC was confirmed based on biopsy of the lesion from extraction site of left lower third molar tooth. We did marsupialization from tooth extraction socket and let it open as a window to apply obturator. The researchers did a serial panoramic radiograph to evaluate treatment, showing reduction of radiolucency size and increasing of FD in lesion peripheral, it means that there was an osseous healing process. One year after marsupialization, the researchers did CBCT examination to evaluate bone regeneration and density. The result of CBCT showed the size reduction of the lesion in sagittal, coronal, and axial planes. CBCT also revealed bone formation from the periphery of the lesion. CBCT assessment and FD analysis of trabecular bone on panoramic radiograph is a reliable imaging method for the treatment evaluation of OKC and determination of ossification as well.